Bioelectrochemical enhancement of the anaerobic digestion of thermal-alkaline pretreated sludge in microbial electrolysis cells. (January 2018) - Xiao, Benyi; Chen, Xia; Han, Yunping; Liu, Junxin; Guo, Xuesong
Abstract: Batch experiments were conducted to study bioelectrochemical enhancement of the anaerobic digestion of thermal-alkaline-pretreated sludge in single-chamber membrane-free microbial electrolysis cells (MECs) with different applied voltage. Experimental results showed bioelectrochemical method could be combined with thermal-alkaline pretreatment to enhance anaerobic digestion of sludge. The methane productions of thermal-alkaline pretreated sludge increased by 20.0%–79.3% when applied voltage was 0.6–1.8 V. The optimal applied voltage was determined as 1.8 V. Water electrolysis did not occur during test under these applied voltages. The removal rates of SCOD and sludge VSS were increased by the applied voltages, with enhanced rates of 2.6–27.6% and 17.1–51.3%, respectively. These applied voltages could enhance the growth of hydrogenotrophic methanogens and inhibit a portion of acetoclastic methanogens. High voltage (up to 1.8 V) was required to produce more methane and reduce more sludge in anaerobic digestion of thermal-alkaline-pretreated sludge when the electrodes of MECs were constructed with special material (Ti/Ru alloy) with a large distance (2 cm). Highlights: MEC and pretreatment were combined to enhance anaerobic sludge digestion. Methane yields were increased by 20.0%–79.3% by applied 0.6 V-1.8 V. The optimal applied voltage was determined as 1.8 V. Decreases in SCOD and sludge concentration were enhanced by applied voltages. Application of 0.6–1.8 V could enhance the growth of hydrogenotrophic methanogens.